1985
DOI: 10.1002/cjce.5450630502
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Taylor vortex structure in combined axial and rotating flow

Abstract: The sequential form of the axial displacement of inclined Taylor vortices and their progressive degeneration to horizontal streaks due to the increasing dominance of axial flow is demonstrated via an analytical indicator-based direct flow visualization technique applied to a concentric cylinder cell with the inner cylinder rotating.Cette communication d6crit le decalage s6quentiel axial des tourbillons de Taylor inclinks, ces derniers se d6sa-gr6geant h la fin en de striures horizontales h la mesure de la domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This zone would seem to correspond to relocation of the vortices in an overall movement at a speed equal to axial speed. This phenomenon has similarly been observed by Astill [48] and by Gu and Fahidy [49]. Lueptow et al [50] carried out a highly meticulous experimental study pertaining to types of flows for low Taylor numbers (Ta < 3000) and very low Reynolds numbers (Re a < 540) in the framework of a narrow cylindrical gap: h ¼ 0.885, e/R 1 ¼ 0.083 and G ¼ 41.…”
Section: Influence Of Rotation: Taylor Vortex Flow Transitionsupporting
confidence: 64%
“…This zone would seem to correspond to relocation of the vortices in an overall movement at a speed equal to axial speed. This phenomenon has similarly been observed by Astill [48] and by Gu and Fahidy [49]. Lueptow et al [50] carried out a highly meticulous experimental study pertaining to types of flows for low Taylor numbers (Ta < 3000) and very low Reynolds numbers (Re a < 540) in the framework of a narrow cylindrical gap: h ¼ 0.885, e/R 1 ¼ 0.083 and G ¼ 41.…”
Section: Influence Of Rotation: Taylor Vortex Flow Transitionsupporting
confidence: 64%
“…Therefore, our results are not limited to PV flow in a Taylor-Couette apparatus only. In this context we also mention the experimental investigation of Gu and Fahidy [23]. They observed that axial through-flow causes a rearrangement of the vortex centers similar to the one seen for tranverse convection rolls subject to a horizontal flow [15, Fig.…”
Section: Scaling Propertiesmentioning
confidence: 85%
“…Only for higher through-flow rates, which are not investigated here, there is a bifurcation [19,20] to spirals [20][21][22][23][24][25][26]. We have performed numerical simulations of the full, rotationally symmetric, two dimensional (2D) Navier-Stokes equations (NSE).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the narrow-gap limit, they also found that the linear theory predicts that axisymmetric vortices form that have a positive axial velocity proportional to the axial flow Reynolds number. Gu and Fahidy (1985;1986) experimentally showed that the effect of axial flow is to decrease wavelength and to increase critical Taylor number. Their range of axial flow Reynolds numbers is substantially higher than Snyder's, starting at Re,=60.…”
Section: Introductionmentioning
confidence: 99%